In-game marriage and computer-mediated collaboration: An exploratory study of Audition - Zhang, Guo; Herring, Susan C. (AoIR Selected Papers of Internet Research, 2013)
This exploratory study discusses how in-game marriage can affect (and effect) Multiplayer Online Game (MOG) players’ collaborative behaviors through an analysis of 2 , a dance battle game released in South Korea in 2004. 2 is a non-violent, non-fantasy MOG which mediates and facilitates couple-related collaborative behaviors. On the basis of a sample of couple-related snapshots (including in-game chat logs, dance battle scenarios, and couple behaviors) collected from an out-game public game forum (n=304) and in-game participant observation (n=126), three types of couple-mediated collaboration in 2 are identified and discussed. This study points to the importance of taking gender (and sexual orientation) into account when analyzing participation in, and the dynamics of, MOG play. In a broader sense, the study of the connection between collaboration and intimacy in MOGs sheds light on the role of digital media in shaping personal relationships.